Handbook of crisis intervention and developmental disabilities - Reed, Derek D.; DiGennaro Reed, Florence D.; Luiselli, James K. (Issues in clinical child psychology., 2013)
The Handbook of Crisis Intervention and Developmental Disabilities synthesizes a substantive range of evidence-based research on clinical treatments as well as organizational processes and policy. This comprehensive resource examines the concept of behavioral crisis in children and adults with special needs and provides a data-rich trove of research-into-practice findings. Emphasizing continuum-of-care options and evidence-based best practices, the volume examines crisis interventions across diverse treatment settings, including public and private schools, nonacademic residential settings as well as outpatient and home-based programs. Key coverage includes: Assessment of problem behaviors. Co-occurring psychiatric disorders in individuals with intellectual disabilities. Family members' involvement in prevention and intervention. Intensive treatment in pediatric feeding disorders. Therapeutic restraint and protective holding. Effective evaluation of psychotropic drug effects. The Handbook of Crisis Intervention and Developmental Disabilities is a must-have resource for researchers, scientist-practitioners, and graduate students in clinical child, school, developmental, and counseling psychology, clinical social work, behavior therapy/analysis, and special education as well as other related professionals working across a continuum of service delivery settings.